Factor structure and psychometric properties of the Perceived Stress Scale in Russian adolescents - Julia Marakshina; Timofey Adamovich; Georgy Vasin; Victoria Ismatullina; Marina Lobaskova; Artem Malykh; Pavel Kolyasnikov; Anna Tabueva; Ilya Zakharov; Sergey Malykh (Scientific Reports, 2024)
Abstract This study involved a psychometric analysis of the 10-item Perceived Stress Scale (PSS-10). To investigate the Russian version of the PSS-10 for adolescents, 3530 adolescents aged 13–17 years were recruited. Confirmatory factor analysis revealed that the data corresponded to the expected two-factor configuration. Psychometric properties and factor structure were evaluated. As expected, the PSS-10 included two factors: perceived helplessness and perceived self-efficacy. Internal consistency demonstrated acceptable values (Cronbach’s alpha was 0.82 for perceived helplessness, 0.77 for perceived self-efficacy, and 0.80 for the overall PSS score). Measurement invariance across sexes was assessed, and configural and metric invariance were confirmed. The developed diagnostic tool can be used both in the school system to alleviate the negative consequences of academic stress in adolescents and, in the future, in other areas, particularly in clinical practice.